Metal-free, visible-light driven C–H ketoalkylation of glycine derivatives and peptides. Issue 23 (10th November 2021) - Xin, Hong; Yuan, Zi-Hang; Yang, Mingyu; Wang, Ming-Hua; Duan, Xin-Hua; Guo, Li-Na
Abstract : A metal free, visible-light driven C–H ketoalkylation of glycine derivatives and peptides with cycloalkyl hydroperoxides is presented. This protocol provides diverse unnatural amino acids bearing a distal carbonyl group in moderate to good yields. Abstract : A metal-free, visible-light driven C–H ketoalkylation of glycine derivatives and peptides with cycloalkyl hydroperoxides is presented. This protocol provides a straightforward route to unnatural amino acids bearing a distal carbonyl group with moderate to good yields. Preliminary mechanistic studies revealed that both a SET event and radical chain propagation were involved in this transformation.